Fashion supply chain and logistics management - Wang, Yi (Routledge, Taylor & Francis Group, 2019)
"The fashion industry has a dynamic, ever changing landscape. The last decade has seen a shift in consumer expectations and a heightened dependence on supply chain management. These shifts in the consumer mentality have already forced apparel retailers to adapt, making changes throughout their organizations to maintain consumer loyalty. This new text provides an overview of the latest trends and advances in fashion supply chain management and logistics, including: The fundamentals of fashion supply chain management Strategic management of the fashion supply chain, including the planning aspect of management ICT in fashion supply chain management RFID and interoperability Drawing on the expertise of academics, researchers and industry experts, including a wealth of real-life cases, this book is an ideal overview for advanced students and academics in fashion management, as well as practising professionals"--Resumé vydavatele